Loss of RBMS1 as a regulatory target of miR-106b influences cell growth, gap closing and colony forming in prostate carcinoma - Dankert, Jaroslaw Thomas; Wiesehöfer, Marc; Wach, Sven; Czyrnik, Elena Dilâra; Wennemuth, Gunther (Scientific Reports, 2020)
Prostate carcinoma (PCa) is the second most commonly diagnosed cancer in males worldwide. Among hereditary genetic mutations and nutrient factors, a link between the deregulation of microRNA (miRNA) expression and the development of prostate carcinoma is assumed. MiRNAs are small non-coding RNAs which post-transcriptionally regulate gene expression and which are involved in tumour development and progression as oncogenes or tumour suppressors. Although many genes could be confirmed as targets for deregulated miRNAs, the impact of differentially expressed miRNA and their regulatory target genes on prostate tumour development and progression are not fully understood yet. We could validate RBMS1, a barely described RNA-binding protein, as a new target gene for oncogenic miR-106b, which was identified as an induced miRNA in PCa. Further analysis revealed a loss of RBMS1 expression in prostate tumours compared to corresponding normal tissue. Overexpression of RBMS1 in DU145 and LNCaP prostate cancer cells resulted in diminished cell proliferation, colony forming ability as well as in retarded gap closing. Our results demonstrate for the first time a miR-106b dependent downregulation of RBMS1 in prostate carcinoma. Additionally, we show new tumour suppressive properties of RBMS1 whose observed loss may further elucidate the development of PCa.
CRIS-Team Scopus Importer:2020-11-06